Towards specialised and differentiated long-term care services: a cross-sectional study - Hanne Marie Rostad; Marianne Sundlisæter Skinner; Ragnhild Hellesø; Maren Kristine Raknes Sogstad (BMC, 2020)
Abstract Background Numerous forces drive the evolution and need for transformation of long-term care services. During the previous decade, primary health care has assumed increased responsibility for developing and providing care services, but there is still limited knowledge about how European care service systems are evolving to address new tasks and patients. Based on data from Norwegian municipalities, this study aims to (1) describe the availability of specialised services in Norwegian nursing homes and home care services and (2) analyse whether structural factors, like population size and/or centrality, are associated with the availability of specialised services in nursing homes and home care. Methods This is a cross-sectional study of survey data. An online survey was designed specifically for this study. Its questions were developed from a comprehensive review of the literature and in partnership with a user panel. One representative from all of Norway's 422 municipalities were invited to answer the survey from February to April 2019. In total, 277 municipalities completed the survey (response rate 66%). Chi-square analysis and Fisher's exact test were used to test the associations between different categorical variables. Results Specialised care services were highly prevalent. For example, there were nursing home units specialising in dementia care (89%) and rehabilitation (81%) and home care teams for dementia care (79%) and reablement (76%). Approximately two-thirds of our sample were categorised as having high availability of specialisation in nursing home and home care services. The larger, more central municipalities had higher availability of specialisation compared to medium-sized and small, less central municipalities. Conclusions Our study indicates that a majority of nursing homes and home care services provide specialised and differentiated services that serve patient groups of different ages and diagnoses. Municipalities' population size and centrality are associated with availability of specialised services in nursing homes and home care services.